Mammal tumours in men. A ten years study. - Lidia Torres Ajá (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2006)
Background: The masculine mammal cancer is extremely infrequent, so many authors consider it as a truly clinical rareness. Objectives: To describe the clinical-pathological behaviour of the mammal cancer in men in the province of Cienfuegos. Method: A descriptive-retrospective study was carried out of all the cases of mammal cancer in men, submitted to surgery in the Universitary Hospital "Dr Gustavo Aldereguia Lima" of Cienfuegos, between January 1996 and December 2005. The variables were: age, affected mamma, topographic localization of the tumour, clinical stage in the moment of diagnosis, histological variant, type of biopsy used, surgical technique applied, and health area. Results: The mayority of cases was registered in the 61-70 age group (44.4%); and respecting benign tumors, it was found in the 31-40 age group with 9 cases (31.3%). An increase incidence was observed in the last seven years, as well as its detection in quite advanced stages. Conclusions: It is necessary to find mechanisms to establish ways of early detection of the mammal tumours in the province, for which it is essential, the clinical personnel preparation and the dispensarization of all the men presenting factors for the mammal tumour.